Influence of training status on cardiac and vascular functioning in young recreational and competitive male rowers - Falcioni, Lavinia; Gallotta, Maria Chiara; Baldari, Carlo; Cardinali, Ludovica; Campanella, Matteo; Ferrari, Dafne; Guidetti, Laura; Meucci, Marco (Frontiers in Pediatrics, 2023)
Introduction The aim of the study was to investigate the influence of training status on cardiovascular function in young male recreational and competitive rowers. Methods Ejection duration in percentage to the heart rate period (ED%), subendocardial viability ratio (SEVR), augmentation index at 75 bpm (AIx75) and carotid to femoral pulse wave velocity (cf-PWV) of competitive rowers (CR) (age 17.6 ± 4.1 years), recreational rowers (RR) (age 16.7 ± 2.70 years) and athletes practicing other recreational sports (ORS) (age 15.3 ± 1.4 years) were assessed. Results ED% was lower in CR compared to ORS (31.9 ± 3.9% vs. 38.4 ± 4.8%; p = 0.026) and cf-PWV was higher in CR compared to ORS (5.5 ± 1.0 m/s vs. 4.7 ± 0.5 m/s; p = 0.032). SEVR was higher in CR compared to RR and ORS (165.8 ± 33.7% vs. 127.4 ± 30.4% and 128.3 ± 27.8%; p = 0.022) and AIx75 was lower in CR compared to RR and ORS (−15.7 ± 8.6% vs. 1.2 ± 9.9% and 1.5 ± 9.1; p = 0.001). Discussion Healthy, young competitive male rowers reported higher myocardial performance and better cardiovascular health than recreational athletes. Interpretations of cf-PWV in competitive rowers should be performed alongside other cardiovascular indicators.